Use of Gestational Surrogates for Women With Marfan Syndrome: A Cost-effectiveness Analysis [16B]. (May 2017) - Clennon, Emily; Caughey, Aaron B.; Teton, Zoe; Shaffer, Brian; Amato, Paula
Abstract : INTRODUCTION: The potential for morbidity in Marfan Syndrome (MS) increases substantially with pregnancy. Though reproductive decision-making among Marfan patients has been described, costs and effectiveness of their reproductive options have not. This study compares costs and outcomes of pregnancy carried by women with MS to pregnancy carried by gestational surrogates. METHODS: A decision-analytic model was built using TreeAge software that compared use of surrogates and pregnancy in women with MS. Outcomes assessed included maternal cardiovascular complication (CVC), intrauterine fetal demise (IUFD), preterm birth, small size for gestational age, and neonatal death. Probabilities and costs were derived from the literature. Utilities were discounted by 3% across the lifespan to generate quality-adjusted life years (QALYs). Univariate and multivariate sensitivity analyses were performed to evaluate robustness of the model. RESULTS: In a theoretical cohort of 10, 000 women with MS, pregnancy would result in 590 maternal CVCs, 22 IUFDs, 1681 preterm births, and 171 neonatal deaths. Use of surrogates would prevent 92% of maternal CVCs, 94% of neonatal deaths, and all but one stillbirth. Cases of preterm birth are also significantly reduced. Surrogate use would save 786, 389 per woman and gain 0.11 QALYs. Cost effectiveness is maintained with high surrogacy cost and low success rate. CONCLUSION: Surrogate use for women with MS is cost effective and significantly improves obstetric outcomes. Benefits are robust in the face of high surrogacy costs due to reduction in maternal CVC and preterm birth. These findings should be used to underscore the importance of broadening health care financing for medically-indicated assisted reproduction.